2021
DOI: 10.1007/s10461-021-03218-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of the COVID-19 Pandemic on HIV Care Utilization, Service Delivery, and Continuity of HIV Antiretroviral Treatment (ART) in Haiti

Abstract: Introduction Our study describes changes in HIV care service delivery and continuity of HIV antiretroviral therapy (ART) for people living with HIV (PLHIV) during the 8 weeks before and after diagnosis of the first coronavirus disease 2019 (COVID-19) cases in Haiti on March 19, 2020. Methods Using data from 96 out of 167 health facilities offering ART services, we compared four ART program indicators: (1) count of HIV visits; (2) proportion of ART dispenses in community-based settings (DAC); (3) proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Undue expenses related to protective equipment, including face masks and sanitizers, were a burden for the people living with HIV. This finding is in agreement with previous findings in Ethiopia ( 14 ) and elsewhere in Africa, wherein sufficient money to buy protective equipment was commonly reported effects of the COVID-19 on attending HIV clinical care and treatment services ( 51 ). The city of Addis Ababa introduced innovative measures providing ART medications for 3 to 6 months to mitigate these challenges.…”
Section: Discussionsupporting
confidence: 93%
“…Undue expenses related to protective equipment, including face masks and sanitizers, were a burden for the people living with HIV. This finding is in agreement with previous findings in Ethiopia ( 14 ) and elsewhere in Africa, wherein sufficient money to buy protective equipment was commonly reported effects of the COVID-19 on attending HIV clinical care and treatment services ( 51 ). The city of Addis Ababa introduced innovative measures providing ART medications for 3 to 6 months to mitigate these challenges.…”
Section: Discussionsupporting
confidence: 93%
“…DSD options have been important in minimizing exposures and ensuring continuity of HIV care during Covid‐19 [ 53 , 54 ]. Mitigation efforts have led to increased eligibility, duration of ART refills and consultations, and community‐based delivery options across sub‐Saharan Africa [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In line with our findings, a cross-sectional survey of MSM in 20 countries from April to May 2020 found that 18% of respondents were unable to or had difficulty refilling their ART prescriptions ( Rao et al, 2021 ). In Haiti, there was an abrupt 18% decline in the proportion of ART refills that were dispensed on time corresponding to the start of the pandemic ( Celestin et al, 2021 ). The proportion of patients who don’t refill prescriptions on time represent perhaps a lower bound on the proportion of patients who have problems with adherence to ART (since these numbers exclude persons who have sufficient ART in their possession but forget to take doses as prescribed).…”
Section: Discussionmentioning
confidence: 99%